2004
DOI: 10.1108/09513540410538831
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice in schools: no justice without trust

Abstract: The concept of organizational justice is defined, and, based on a review of the literature, ten principles of organizational justice are elaborated. Similarly, the elements of faculty trust are conceptualized and discussed. Then, a model of organizational justice and trust is proposed and tested using path analysis. The results underscore the symbiotic relations between trust and justice. The paper concludes with a few suggestions for future research and recommendations for practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
1
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(219 citation statements)
references
References 24 publications
(39 reference statements)
9
159
1
22
Order By: Relevance
“…It culminates in their being intolerant of others. This is consistent with the view that perception of justice become justice (Hoy and Tarter, 2004). The same holds true for injustice.…”
Section: Misconceptions About Shared Decision-makingsupporting
confidence: 79%
“…It culminates in their being intolerant of others. This is consistent with the view that perception of justice become justice (Hoy and Tarter, 2004). The same holds true for injustice.…”
Section: Misconceptions About Shared Decision-makingsupporting
confidence: 79%
“…Other studies conducted in the literature support this finding as well. In the studies conducted by Brockner et al, 1997;Hoy and Tarter, 2004;Polat, 2007;Polat and Celep, 2008;Kaya, 2013;Şentürk, 2011;Kılıçlar, 2011;Günaydın, 2011 andBaş andŞentürk, 2011. It was found that the concepts of organizational trust and justice were related with each other and justice in organization affects the concept of trust and vice versa.…”
Section: Extended Abstractmentioning
confidence: 99%
“…He also tries to provide support in times of grief and celebrate individual teachers' achievements with them, even when these are not work related. This reflects the open, sensitive and authentic treatment of teachers expected from social justice leaders [21].…”
Section: Making a Difference To Teachers And The Curriculummentioning
confidence: 99%
“…This view gives social justice leadership an activist slant that extends beyond the confines of schools. As leaders who seek to transform their schools into socially just entities, principals should, among other attributes: be exemplary on social justice issues [42 and 43] [emphasis mine]; be open, sensitive and authentic in the treatment of teachers [21]; question institutional culture and assumptions that inform school policies and practices [5, 7 and 13]; alter inequalities related to the abuse of social power [9 and 18]; create a climate that fosters a sense of belonging to all school community members [43]; prioritise the elimination of marginalising conditions like race, class, gender, disability, sexual orientation [5, 42 and 43]; create learning opportunities and maintain high expectations of all learners [5 and 37]; encourage critical reflection on, and commitment to social justice among teachers [7 and 37].…”
Section: Conceptual Framework and Related Literaturementioning
confidence: 99%